The Role of Ubiquitin-specific Peptidases in Colorectal Cancer: A Systematic Review Protocol - Al-Balushi, Eman; Al-Marzouqi, Amina; Tavoosi, Shima; Baghsheikhi, Amir Hossein; Sadri, Arash; Sharifi Aliabadi, Leyla; Salarabedi, Mohammad-Mahdi; Rahman, Syed Azizur; Al-Yateem, Nabeel; Mosavi Jarrahi, Alizera; Halimi, Aram; Ahmadvand, Mohammad; et al. (Asian Pacific Journal of Cancer Biology, 2023)
Background: This systematic review aims to comprehensively assess and synthesize the current body of evidence regarding the role of ubiquitin-specific peptidases in colorectal cancer. Methods: This protocol adhered to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol (PRISMA-P) and was officially registered with the International Prospective Register for Systematic Reviews (PROSPERO) under the registration number CRD42022348183. Results: This study will provide a concise summary of the synthesized data from the included studies and will synthesize key findings, explore clinical and therapeutic implications, address limitations and gaps in knowledge, and propose avenues for future research. Conclusion: This section will conclude by summarizing the key takeaways from the systematic review and emphasizing the relevance of the findings in advancing our knowledge of the role of USPs in colorectal cancer. It will also underscore the potential implications for clinical practice and future research directions.